STUDENTS GENERATED QUESTION QUALITY THROUGH STEM BASED PROJECT LEARNING IN SCIENCE ACTIVITY - Nurramadhani, Annisa; Permana, Irvan (UNIVERSITAS PAKUAN, 2020)
STEM based project learning also capable triggering student to express another higher order thinking skill, such as inquiry by posing question. Generating questions, making comparisons, dealing with contradictions, and scientific inquiry skills are an example of cognitive activities that are classified as higher-order thinking skills. Those skills are including in 21st century skills that needed by the students to face the workspaces demanding in this revolution industry 4.0 and future. The purposes of this research is to investigate students question quality through STEM based project learning in science activity. The method that is used in this research is descriptive. The subject in this research are the students of preservice teacher biology and science education for about 21 students. The research needs an analysis of students generated question quality when they are in basic physics laboratory activity. This laboratory activity used STEM based project learning approach with reading assignment in the early meeting before each laboratory activity. The technique to take the data that is used in this research are video recording, observation, and informal interview. The research instrument to take the data that is used are observation sheet for students generated question quality. The result of this research is from the science laboratory activity, students generated question quality that has the most are understanding and relationship which is in the beginning of open question quality and information category gained lower than both of category. It means that, students promoting the improvement of their question quality. It also proved that evaluating, finding and solution category has expressed by the students in both of laboratory activities. It can be concluded that that the quality of students generated question has slightly improved to open question quality through STEM based project learning in science activity